Organisation of the sympathetic skin response in spinal cord injury. Issue 3 (1st March 2002) - Cariga, P; Catley, M; Mathias, C J; Savic, G; Frankel, H L; Ellaway, P H
Abstract : Objectives: The sympathetic skin response (SSR) is a technique to assess the sympathetic cholinergic pathways, and it can be used to study the central sympathetic pathways in spinal cord injury (SCI). This study investigated the capacity of the isolated spinal cord to generate an SSR, and determined the relation between SSR, levels of spinal cord lesion, and supraspinal connections. Methods: Palmar and plantar SSR to peripheral nerve electrical stimulation (median or supraorbital nerve above the lesion, and peroneal nerve below the lesion) were recorded in 29 patients with SCI at various neurological levels and in 10 healthy control subjects. Results: In complete SCI at any neurological level, SSR was absent below the lesion. Palmar SSR to median nerve stimuli was absent in complete SCI with level of lesion above T6. Plantar SSR was absent in all patients with complete SCI at the cervical and thoracic level. In incomplete SCI, the occurrence of SSR was dependent on the preservation of supraspinal connections. For all stimulated nerves, there was no difference between recording from ipsilateral and contralateral limbs. Conclusions: No evidence was found to support the hypothesis that the spinal cord isolated from the brain stem could generate an SSR. The results indicate that supraspinal connections are necessary for the SSR, together with integrity of central sympathetic pathways of the upper thoracic segments for palmar SSR, and possibly all thoracic segments for plantar SSR.